Hydroxide melt induced corrosion of Ni at elevated temperatures under steam electrolysis conditions. (13th August 2021) - Anisur, M.R.; Aphale, Ashish; Raman, R.K. Singh; Dubey, Pawan Kumar; Hong, Junsung; Reisert, Michael; Heo, Su Jeong; Lattimer, Judith; Patil, Kailash; Xu, Hui; Yuh, Chao-Yi; Singh, Prabhakar
Abstract: Molten alkali electrolyte based high temperature water electrolysis (HTWE) process offers an efficient pathway to integrate renewable energy resources for large scale and economic hydrogen production. Long term and stable operation of these systems require an in-depth understanding of materials stability under anodic and cathodic exposure conditions of the cell and cell stacks. In the present study, we report our findings on the corrosion of Ni in the presence and absence of (Li–Na) hydroxide melt at 600 °C under oxidizing and reducing conditions representative of HTWE. While the Ni electrode was found to remain thermodynamically stable in metallic form under cathodic (reducing) exposure conditions, the corrosion rate in molten hydroxide under oxidizing conditions was found to be non-parabolic in nature. A cyclic voltammetry study provides the breakdown of the passive metal-oxide surface layer at the anodic overpotential region between 0.45 V and 2 V in molten hydroxide under oxidizing conditions. A thermochemical process for accelerated corrosion based on the oxide scale fluxing in hydroxide melt has been developed. Highlights: A porous oxide scale forms on Ni in molten hydroxide under oxidizing conditions. Oxide scale growth in the presence of molten hydroxide is non-parabolic. Ni remains metallic in molten hydroxide under reducing conditions.